Anatomia dos tegumentos das sementes do quiabeiro (Hibiscus esculentos L) e o uso de substâncias químicas para acelerar a germinação - V L Medina , Paulo; M T Medina , Regina; Shimoya, Chotaro (Revista Ceres, 2025)
The objective of this study was to test the effect of the pre-treatment of okra seed on germination, as well as to study certain anatomic aspects of the okra seed coat.